Analisis Kekuatan Miniatur Sasis Bus Hasil Teknologi Fused Deposition Modelling dengan Metode Elemen Hingga - Braam Delfian Prihadianto; Ari Reza Koswara (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
Replica is an imitation of an object that is scaled down to a specified scale. Replica manufacturing can be done by layer manufacturing technology so that it is more efficient and gets products similar to the originals. At present, the information about the results of the experimental testing process by computers on replica 3D models is still very limited. It is important to know that the replica have the expected quality. This study was conducted to determine the replica strength of the Hino RN 285 bus chassis 1:19 scale with PLA and AISI 1020 material. The calculations included stresses and deflections that occurred on the replica bus chassis due to the load from the replica cabin of 25.506 N. The study was conducted using Solidworks 2018 application for static load simulation process and for knowing the maximum stress and deflection that occurred. The simulation results obtained a maximum strenght value of 9,628 MPa. Deflection occurs at the front overhang, wheel base, and rear overhang with a maximum value occurs at the rear overhang of 0.7696 mm and causes stress distribution on the chassis frame of the rear overhang at 2.407 MPa. The maximum stress of the test results has a value smaller than the yield stress of the material and the deflection that occurs is below the critical deflection range, so it can be concluded that the replica model of the bus chassis is safe.